Multivariate analysis of phenological, pomological and fruit quality characters in apricot (Prunus armeniaca) grown in trans-Himalayan Ladakh region, India - KOREKAR, GIRISH; YADAV, ASHISH; KUMAR, RAJ; SRIVASTAVA, RAVI B; STOBDAN, TSERING (The Indian Journal of Agricultural Sciences, 2013)
The purpose of this study was to contribute to the phenological, pomological characteristics and fruit quality specification of 17 apricot genotypes grown under similar cultural practices in trans-Himalayan Ladakh region. A total of 27 characters were analyzed during the two years of study course. A wide variation in bud break season, blossom season, harvest season, fruit size, stone mass, TSS and total acidity was observed. Except for one genotype, fruit weight from all other genotypes were determined <=35.1 g, which shows that apricot fruit of Ladakh region are mainly composed of low fruit weight genotypes. All the evaluated genotypes showed high TSS content ranging from 16.1-20.6%. Significant correlation within the pomological and phenological characteristics was observed. The correlation between fruit development period and fruit weight is low, indicating that fruit size is not simply determined by the number of days from end of blossoming to fruit harvest period. Eigenvectors resulting from Principal Component Analysis show that more than 57% of the variation is explained by the first three principal components (PC1-PC3).